A new stigmaeid mite species from Iran (Acari: Stigmaeidae) and re-description of Stigmaeus longipilis (Canestrini) - Yali, Maryam Pahlavan; Khanjani, Mohammad; Razmjou, Jabraeil (Zootaxa, 2011)
A new species of the genus Stigmaeus, S. ueckermanni sp. nov., is described and illustrated, and S. longipilis (Canestrini) is recorded for the first time from Iran and re-described. Both species were collected from soil under hazelnut trees, Corylus avellana L. (Betulaceae) in Ardabil province, Iran. A key to the Iranian species of Stigmaeus is provided.